Predictors of Postoperative Epilepsy/Seizures in Patients Readmitted After Meningioma Resection - Rasha Elbadry; Anthony O. Asemota; Brandon Edelbach; Lei Huang; Firas Bannout; Warren Boling (Behavioural Neurology, 2025)
Conclusion: Development of epilepsy/seizures after meningioma resection is likely multifactorial. Identifying factors associated with postoperative epilepsy/seizures after discharge is important in triaging and closer monitoring of at-risk patients and for adapting management to help improve outcomes.